2019
DOI: 10.1128/msphere.00454-19
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Meta-omics Reveals a Fungus-Associated Bacteriome and Distinct Functional Pathways in Clostridioides difficile Infection

Abstract: There has been no prior application of matched metagenomics and metatranscriptomics in Clostridioides difficile infection (CDI) evaluating the role of fungi in CDI or identifying community functions that contribute to the development of this disease. We collected diarrheal stools from 49 inpatients (18 of whom tested positive for CDI) under stringent inclusion criteria. We utilized a tiered sequencing approach to identify enriched bacterial and fungal taxa, using 16S and internal transcribed spacer (ITS) rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 38 publications
3
55
4
Order By: Relevance
“…Their findings demonstrated an increase in the family Pichiaceae of the order Saccharomycetales , while in CDI patients, relative abundance was observed in the phylum Ascomycota , the order Pleosporales and the class Dothideomycetes . This interkingdom interaction in CDI patients was recently reported by Stewart et al, 98 who showed an abundance of Aspergillus and Penicillium taxa in CDI patients, which were negatively correlated with the presence of some bacterial taxa; Oscillospira , Comamonadaceae , Microbacteriaceae and Cytophagaceae . Taken together, it seems that bilateral interaction between fungi–bacteria could be an important factor involving in the pathophysiology of CDI.…”
Section: Correlation Between the Gut Mycobiome And The Gut Bacteriasupporting
confidence: 79%
“…Their findings demonstrated an increase in the family Pichiaceae of the order Saccharomycetales , while in CDI patients, relative abundance was observed in the phylum Ascomycota , the order Pleosporales and the class Dothideomycetes . This interkingdom interaction in CDI patients was recently reported by Stewart et al, 98 who showed an abundance of Aspergillus and Penicillium taxa in CDI patients, which were negatively correlated with the presence of some bacterial taxa; Oscillospira , Comamonadaceae , Microbacteriaceae and Cytophagaceae . Taken together, it seems that bilateral interaction between fungi–bacteria could be an important factor involving in the pathophysiology of CDI.…”
Section: Correlation Between the Gut Mycobiome And The Gut Bacteriasupporting
confidence: 79%
“…The microbiota is composed of viruses, fungi, and parasites in addition to bacteria, and these nonbacterial members can also vary across sources of mice ( 55 , 56 ). While our study focused solely on the bacterial portion, viruses and fungi have also begun to be implicated in the context of CDIs or fecal microbiota transplantation (FMT) treatments for recurrent CDIs ( 34 , 57 60 ). Beyond community composition, the metabolic function of the microbiota also has a CDI signature ( 19 , 46 , 61 , 62 ) and can vary across mice from different sources ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of eukaryotes in the development of CDI has been addressed in only a few investigations in which the involvement of fungi was emphasized 13 , 14 . Among the main findings was an increase in the relative abundance of fungi of the genus Penicillium in patients with CDI compared with patients without CDI 15 , as well as a relationship between C. albicans and failures in fecal transplant treatment 16 .…”
Section: Introductionmentioning
confidence: 99%